Strategi Komunikasi Pedagang Kaki Lima Perantau Minangkabau Dan Penduduk Asli - E. Arif (Jurnal Komunikasi Pembangunan, 2012)
Abstract Retail dealer originated is one of the informal sectors which are deeply involved by some of group societies. One of them come from ethnic of Minangkabau who live in Jatibarang market. In the Jatibarang market, retail dealer originated not only come from Minang ethnics but also natives. The aim of this research are: (1) to analyzed the difference of communications strategy retail dealer originated of Minangkabau ethnics compare with natives in Jatibarang market, (2) to analyzed the relation of communications strategy retail dealer originated between Minangkabau ethnics and natives with perception of buyer concerning understanding, motivation and fascination buy, (3) to formulate effective communications strategy for retail dealer originated in Jatibarang market. Research method used descriptive of data and correlation analysis with SPSS version 12.00 program. Test of statistic used Rank Spearman to see the relation between test and variable. T-Test was used to see the difference between two merchants. Amount of responders counted 60 buyer people. Result of research showed: (1) communications strategy retail dealer originated of Minangkabau ethnics using verbal and non verbal, so do the natives. (2) by verbal, there were no difference between retail dealer originated of Minang ethnics and natives. But by non verbal there were differences. (3) Buyer had low perception in understanding to retail dealer originated of minang ethnics, high in fascination and also high in motivation to buy. While of natives merchant, buyer also low in understanding, average in fascination and high in motivation to buy. (4) Communications strategy of verbal at retail dealer originated of Minang ethnics had relation with understanding, motivation and fascination to buy. By non verbal only relating to understanding. While at retail dealer originated of natives, by verbal relate to understanding and by non verbal with fascination and understanding. (5) Effective communications strategy for retail dealer originated in Jatibarang market was by verbal address and passes in, while by non verbal smile, body position and display the products. Keyword: communications strategy of retail dealer originated, perception of buyer, communications effectiveness